2022
DOI: 10.1111/gcb.16497
|View full text |Cite
|
Sign up to set email alerts
|

Toward a forest biomass reference measurement system for remote sensing applications

Abstract: Forests contribute to climate change mitigation through carbon storage and uptake, but the extent to which this carbon pool varies in space and time is still poorly known.Several Earth Observation missions have been specifically designed to address this issue, for example, NASA's GEDI, NASA-ISRO's NISAR and ESA's BIOMASS. Yet, all these missions' products require independent and consistent validation. A permanent, global, in situ, site-based forest biomass reference measurement system relying on ground data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…Finally, we recommend adopting a context-aware approach in the growing number of forest AGB mapping projects [9,11,130]. Likewise, we recommend using metrics entirely locally computed (e.g., S L i ) to detect local patterns and leverage their use, as suggested by Westerholt et al (2018) [79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we recommend adopting a context-aware approach in the growing number of forest AGB mapping projects [9,11,130]. Likewise, we recommend using metrics entirely locally computed (e.g., S L i ) to detect local patterns and leverage their use, as suggested by Westerholt et al (2018) [79].…”
Section: Discussionmentioning
confidence: 99%
“…This is a considerable undertaking, since the technology, data sources and methods employed at different scales vary greatly, making it difficult to track propagated errors [6], or to determine how different end-products (i.e., AGB maps) perform comparatively [7]. This lack of standardization results in AGB and trait-mapping products with different degrees of agreement, making it particularly relevant to compare data-acquisition methods [8] and validation procedures [7,9] of the AGB products [10,11]. In this scenario, Unmanned Aerial Vehicle (UAV) & Light Detection and Ranging (LiDAR) monitoring systems are regarded as particularly versatile [12], accurate and cost-effective [13] tools to be bridged to regional scale maps seamlessly [6] Current RS-driven biomass research focuses on algorithmic developments for the detection and segmentation of single trees, in order to enable more precise estimates of structural tree traits [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ground‐based biomass stocks and fluxes are widely used to estimate carbon budgets, to quantify forest carbon offsets, and to calibrate and validate remote sensing products used to obtain biomass estimates at regional and global scales (Cabon et al, 2022; Chave et al, 2019; Duncanson et al, 2019; Labrière et al, 2022; Xu et al, 2021). In this study, we showed that biomass loss from damage to living trees constitutes an important and overlooked component of biomass loss across seven tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…Landsat 8, GEDI, BIOMASS, NISAR) dedicated to measuring land dynamics, forest structure and biomass using a combination of sensor types (Quegan et al 2019, Dubayah et al 2020. Secondly, there is an unprecedented degree of collaboration between international groups on harmonizing methods and improving the accuracy and policy-relevance of EO products (Szantoi et al 2020, Tsendbazar et al 2021, Araza et al 2022, Labriere et al 2022. Finally, partnerships with technology platforms allow free and easy dissemination and processing of EO products (Gorelick et al 2017) which should facilitate their uptake in reports to the UNFCCC and support the operationalization of the Paris Agreement (table 1).…”
Section: Element Of the Paris Agreementmentioning
confidence: 99%